Upholding Tuberculosis Services during the 2014 Ebola Storm: An Encouraging Experience from Conakry, Guinea. - Nimer Ortuno-Gutierrez; Rony Zachariah; Desalegn Woldeyohannes; Adama Bangoura; Gba-Foromo Chérif; Francis Loua; Veerle Hermans; Katie Tayler-Smith; Welile Sikhondze; Lansana-Mady Camara (PLoS ONE, 2016)
Ten targeted health facilities supported by Damien Foundation (a Belgian Non Governmental Organization) and the National Tuberculosis (TB) Program in Conakry, Guinea.To uphold TB program performance during the Ebola outbreak in the presence of a package of pre-emptive additional measures geared at reinforcing the routine TB program, and ensuring Ebola infection control, health-workers safety and motivation.A retrospective comparative cohort study of a TB program assessing the performance before (2013) and during the (2014) Ebola outbreak.During the Ebola outbreak, all health facilities were maintained opened, there were no reported health-worker Ebola infections, drug stockouts or health staff absences. Of 2,475 presumptive pulmonary TB cases, 13% were diagnosed with TB in both periods (160/1203 in 2013 and 163/1272 in 2014). For new TB, treatment success improved from 84% before to 87% during the Ebola outbreak (P = 0.03). Adjusted Hazard-ratios (AHR) for an unfavorable outcome was alwo lower during the Ebola outbreak, AHR = 0.8, 95% CI:0.7-0.9, P = 0.04). Treatment success improved for HIV co-infected patients (72% to 80%, P<0.01). For retreatment patients, the proportion achieving treatment success was maintained (68% to 72%, P = 0.05). Uptake of HIV-testing and Cotrimoxazole Preventive Treatment was maintained over 85%, and Anti-Retroviral Therapy uptake increased from 77% in 2013 to 86% in 2014 (P<0.01).Contingency planning and health system and worker support during the 2014 Ebola outbreak was associated with encouraging and sustained TB program performance. This is of relevance to future outbreaks.